“Camera Based Product Information Reading For Blind People” (International Journal of Engineering and Computer Science, 2017)
Nowadays printed text appears everywhere like product names, restaurant menus, instructions on bottles, signed boards etc. Thus blind people need some assistance to read this text .This paper presents a camera-based product information reader to help blind persons to read information of the products. Camera acts as main vision in detecting the label image of the product then image is processed internally and separates label from image by using MATLAB and finally identifies the product name and identified product information is pronounced through the optical character recognition (OCR).The OCR is used to convert the text from text regions and then converted to voice output.